A responsabilidade social da empresa atraves da autorregulacao regulada - Maia, Annuska Macedo Santos de França Paiva (2019)
The thesis stablishes Corporate Social Responsibility (CSR) as a category of interest to the Law, linked to the companies social function, under jurisdictional control, to put on effect public development objectives. The problem asks which would be the adequate regulatory framework to ensure that CSR promotes Human Rights. National and foreign casuistic analysis reveals that free self-regulation, with directives of voluntary adoption, is not enough to hinder violations of fundamental rights by companies. Direct observation of the UN binding-treaty discussions inserts human rights negotiations in the diplomatic domain, but with little effectiveness, thus the search for regional or nationalized parameters to integrate social responsibilities into companies remains justified. In a return to the elaboration of CSR academic concept, it is clear that the profusion of definitions drove the institute away from social concerns, contrary to the wishes of Howard Bowen, its fundamental author. This gap is attacked by regional and independent national legislations with varying degrees of effectiveness. The European Union has issued a national legislation-generating directive on non-financial reporting obligations based on international frameworks such as the Guiding Principles, the Global Compact and the UN Sustainable Development Goals, and ISO 2600: 2010, however the lack of control mechanisms challenges their relevance. Although the Organization of American States published a Guide of Principles on Corporate Social Responsibility in the Americas, its detailed analysis reveals the maintenance of voluntary logic, with little impact on the bloc. India and Mauritius set laws on minimum spending and areas for CSR funding: the social effectiveness of this legislation is discussed, as there is a disconnection between programs and business activity and the reduction of CSR to funding obligations, without breaking the philanthropic-voluntarist perspective of corporate responsibility. France innovates by prescribing due diligence obligations to the entire production chain, with the possibility of holding French companies accountable even for events occurring beyond the national territory. Recent CSR-related Brazilian public policies have failed to integrate themselves and with the judicial system: the axes of the National Investment and Impact Business Strategy did not influence other legislative actions, as observed by the surprise approval of the National Guidelines on Business and Human Rights, unconnected to the previous multisectoral discussions. This thesis modifies the CSR conceptual pyramid, placing the link between business activity and human rights - including sustainable socio-environmental and economic development – as a basis of social responsibility. Thus, the company, from the very development of its economic activity, should map, solve and remedy their negative impacts, and socially operate in a positive way to local communities and other stakeholders, contributing to development. These actions should be publicized through a report, which can be used by the state and organized civil society, to hold companies liable in case of inconsistencies of information. Therefore, CSR is under a regulated selfregulation framework, as companies will freely define their corporate social responsibility policies, but with the possibility of social control through legal instruments provided by national legislation.